2018
DOI: 10.1111/ger.12327
|View full text |Cite
|
Sign up to set email alerts
|

Review: An overview and analysis of novel oral anticoagulants and their dental implications

Abstract: Despite these benefits, as well as various others, NOACs still lack specific management parameters as well as antidotes or reversal agents. Therefore, dental professionals must use caution when treating patients currently taking these specific anticoagulants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…In the end, five articles could be included as they met the inclusion criteria (►Fig. 1). ►Table 1 describes the selected studies.…”
Section: Resultsmentioning
confidence: 99%
“…In the end, five articles could be included as they met the inclusion criteria (►Fig. 1). ►Table 1 describes the selected studies.…”
Section: Resultsmentioning
confidence: 99%
“…Several randomized trials demonstrated that canceling DAPT therapy increase the risk of stent thrombosis which can occur in short period of time or as a late complication [2,26,27]. It is associated with a high rate of myocardial infarction and a short-term mortality rate of up to 50-70% [2,17].…”
Section: Discussionmentioning
confidence: 99%
“…Withdrawing anticoagulant therapy could lead to ischemic stroke potentially resulting in disability or death. Therefore, maintaining both therapies is vital in the prevention of major adverse cardiac events [26][27][28][29]. Although both DAPT and NOAC therapy might cause bleeding complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the case of a patient under treatment with Rivaroxaban who had multiple minor bleeding episodes several days after the dental implant surgery, C Kim et al indicated the cessation of NOACs [26]. Recently, in a review published in 2018 by K Fortier et al, the cessation of Dabigatran, Rivaroxaban, Apixaban and Edoxaban was indicated in all dental surgery interventions, regardless of the high or low risk of bleeding [27][28][29].…”
Section: Mrd000576 3(5)2019mentioning
confidence: 99%